Faktor-Faktor Bauran Pemasaran Yang Menumbuhkan Minat Beli Konsumen Pada Produk Eiger Di Karanganyar - Hidup Marsudi; Wening Nalurita (Riset Manajemen dan Akuntansi, 2026)
This study aims to examine the effect of product quality, price, promotion and distribution on the purchasing power of Eiger products in Karanganyar This type of research is quantitative and uses data collection techniques through the distribution of questionnaires, interviews, observations and literature studies using the Accidental sampling approach with 100 respondents. While the data analysis method used includes analysis of research instruments consisting of validity tests, reliability tests, classical assumption tests, multiple linear regression tests. The results of this study that using the t test shows that the product quality variable has a significant effect on consumer purchasing power, while through the f test it can be seen that together the four variables affect consumer purchasing power. The adjusted R square figure is 0.970 or 97.0%. Based on the results of this study, the variables of product quality, price, promotion and distribution partially or simultaneously have an effect on consumer purchasing power on Eiger products in Karanganyar